2022
DOI: 10.1186/s12864-022-08834-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of chloroplast genomes from Six Rhodiola species: variable DNA markers identification and phylogenetic relationships within the genus

Abstract: Background As a valuable medicinal plant, Rhodiola has a very long history of folk medicine used as an important adaptogen, tonic, and hemostatic. However, our knowledge of the chloroplast genome level of Rhodiola is limited. This drawback has limited studies on the identification, evolution, genetic diversity and other relevant studies on Rhodiola. Results Six Rhodiola complete chloroplast genomes were determined and compared to another Rhodiola c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This study sequenced and assembled the plastomes of 23 samples from 18 Rhodiola species, analyzing structural features, codon usage bias, repeat sequences, comparative genomics, and phylogenetic relationships. The length of Rhodiola plastomes ranges from 150,893 bp to 151,946 bp, and the genome size, gene order, gene number, and genome structure are highly conserved within Rhodiola plastomes, which is consistent with previous research (Zhao et al, 2022). In the codon analysis, we found that the average number of codons for Rhodiola species was greater than that for species distributed over a wide geographical range, such as Arabidopsis thaliana.…”
Section: Discussionsupporting
confidence: 90%
“…This study sequenced and assembled the plastomes of 23 samples from 18 Rhodiola species, analyzing structural features, codon usage bias, repeat sequences, comparative genomics, and phylogenetic relationships. The length of Rhodiola plastomes ranges from 150,893 bp to 151,946 bp, and the genome size, gene order, gene number, and genome structure are highly conserved within Rhodiola plastomes, which is consistent with previous research (Zhao et al, 2022). In the codon analysis, we found that the average number of codons for Rhodiola species was greater than that for species distributed over a wide geographical range, such as Arabidopsis thaliana.…”
Section: Discussionsupporting
confidence: 90%
“…Aizoon (Table 1). In addition, the overall genome size, gene numbers, and GC content were like those of the sister lineage Rhodiola and other closely related genera (Hylotelephium, Kalanchoe, Orostachys, Rosularia, Sedum, Sinocrassula, and Umbilicus) (Kim and Kim, 2020;Zhao et al, 2020;Zhao et al, 2022). This suggests that despite being morphologically and cytologically extremely variable, major lineages of the subfamily Sedoideae have highly conserved plastomes.…”
Section: Discussionmentioning
confidence: 74%
“…This suggests that despite being morphologically and cytologically extremely variable, major lineages of the subfamily Sedoideae have highly conserved plastomes. In the case of the hypervariable regions of plastomes ( Figure 3 ), which can be used as barcoding markers, we identified one ycf1 gene and three intergenic regions ( trnH – psbA , ndhF – rpl32 , and trnW – trnP ), which showed high sequence variation in the two sister lineages Rhodiola and Phedimus ( Zhao et al., 2022 ). These sets of mutation hotspots in the two sister genera could provide useful phylogenetic information for phylogeographic and population genetic studies at the intraspecific level.…”
Section: Discussionmentioning
confidence: 99%
“… 2020 ), Rhodiola kirilowii MT937183 (Zhang and Liu 2021 ), Rhodiola quadrifida OL742463 (Zhao et al. 2022 ), Rhodiola dumulosa MN794323 (Zhao et al. 2020 ), Rhodiola tangutica NC060605 (Lakshmanan et al.…”
Section: Resultsmentioning
confidence: 99%